1990
DOI: 10.1007/bf02380951
|View full text |Cite
|
Sign up to set email alerts
|

Survey and census of the hoolock gibbon in West Garo Hills, Northeast India

Abstract: ABSTRACT. During a long-term study on the hoolock gibbon in Northeast India, a detailed survey was made in West Garo Hills District of the Meghalaya, India from July 1985 to March 1987. Approximately 5,075 km 2 of the area was covered. Groups and individuals were counted in 32 localities (812 km2). Interestingly only 1,395 ha was the actual forest area occupied by these gibbons. Fortytwo family groups and four floating individuals of gibbons made up the total count. Of these the adult males and females compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…hoolock are monogamous and maintain a social network within a group and social proximity with neighbouring groups of the same species [Alfred and Sati, 1990]; these authors also reported that a typical family group consists of a mated pair and 1-3 immature offspring. However, solitary individuals were also found near an existing group [Alfred and Sati, 1990]. During the present study, 1 solitary subadult (male) individual was found.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…hoolock are monogamous and maintain a social network within a group and social proximity with neighbouring groups of the same species [Alfred and Sati, 1990]; these authors also reported that a typical family group consists of a mated pair and 1-3 immature offspring. However, solitary individuals were also found near an existing group [Alfred and Sati, 1990]. During the present study, 1 solitary subadult (male) individual was found.…”
Section: Resultsmentioning
confidence: 98%
“…a mean group size of 3.6 individuals for 9 groups, is closely comparable to other studies conducted in different parts of the H. hoolock distribution range, as reported in Kumar et al [2009], i.e. 3.2 individuals for 24 groups and 3.4 for 7 groups [Tilson, 1979], 3.1 for 8 groups and 3.0 for 14 groups [Choudhury, 1990[Choudhury, , 1991 in Assam, 3-3.2 for 6-10 groups [Mukherjee, 1982], 2.1 for 34 groups [Gupta, 1994] in Tripura, 3.0 individuals for 42 groups [Alfred and Sati, 1990] in Meghalaya, 3.5 for 6 groups [Gittins and Tilson, 1984], 2.3 for 5 groups and 2.9 for 15 groups [Ahsan, 1984[Ahsan, , 1994, and 2.9 for 13 groups [Feeroz and Islam, 1992] in Bangladesh ( table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…With habitat fragmentation, the hardest hit species are the hoolock gibbons, Phayre's langurs, Bengal slow lorises, and capped langurs. It is projected that if jhum cultivation continues, the gibbons will eventually disappear from these places because they require continuous canopy in order to thrive (Alfred and Sati, 1990;Gupta and Kumar, 1994;Mukherjee et al, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…It is one of the most extensively studied primates, and an extensive literature is available on the animal from various regions of northeast India (Alfred and Sati, 1990;Choudhury, 1990aChoudhury, , 2000bChoudhury, , 2006bChoudhury, , 2009aChoudhury, , 2009bMukherjee et al, 1992).…”
Section: Different Primates Of Southern Assammentioning
confidence: 97%
“…For gibbon surveys, researchers more frequently use auditory as opposed to visual cues (but see Alfred and Sati 1990). Haimoff et al (1986) located 20 groups during a survey of black-crested gibbons (Nomascus concolor) through auditory cues, only six of which were sighted.…”
Section: Sightings and Auditory Samplingmentioning
confidence: 99%